Prescription pattern in the department of medicine in a tribal district hospital of India - Mohammed Shakeel Mohammed Bashir; Ajay Khade1; Pandit Kishanrao Deshmukh; Anil Mamidi (Al Ameen Medical College, 2013)
Objectives: Drug utilization studies can be used as a tool for evaluation of health care system. Hence, the study was conducted in a tribal district hospital of south India to evaluate the prescription pattern which could be useful for improvement of health care facilities in the region. Materials and Methods: A total of 50 cases belonging to general medicine department were selected randomly in this retrospective study. Only hospitalized cases were included and all the OPD cases were excluded from the study. Results: Common age group was in between 21 to 30 years. Commonest cause of hospitalization was febrile illness. Average number of drugs per prescription was 4.64. Most preferred route was intravenous route. Antimicrobials were the most frequently prescribed drugs and ampicillin (29.73%) was the commonest amongst them. All the cases were managed by empirical treatment. In most of the patient mono antimicrobial therapy was given. 40% drugs were prescribed by generic name. Dose of most of the drugs was inappropriate. Conclusion: We conclude that there is an urgent need for correction of some irrational approaches.